Peningkatan Kemampuan Pemahaman Matematis dan Self Confidence Melalui Pembelajaran Kooperatif Tipe Group Investigation pada Siswa Sekolah Dasar - Edison Edison; Sowanto Sowanto (SUPERMAT : Jurnal Pendidikan Matematika, 2021)
This study aims to analyze the increase in students' mathematical understanding ability and self-confidence as a result of the application of group investigation type cooperative learning. This research is quasi-experimental research, with the design used being "nonequivalent groups pretest-posttest design". The sample in this study were all fifth-grade students at one of the public elementary schools in Sumedang Regency. The instruments used in this study were a test of mathematical understanding ability and a Likert scale questionnaire to analyze students' self-confidence. Statistical analysis used in this study was independent sample t-test, Mann-Whitney U, one-way ANOVA, and two-way ANOVA. The results of this study indicate that when viewed based on learning factors, there are differences in the increase in mathematical understanding abilities and self-confidence between students who study with group investigation type cooperative learning compared to students who learn by direct learning; there is no interaction effect between learning factors and early mathematical ability factors; there is a difference in the effect of increasing students' mathematical understanding abilities who study with group investigation type cooperative learning in terms of students' initial mathematical abilities (high, medium, and low).